Tecnology FPV Camera Gimbal Controller Design Synchronized with the SS2 Weapons Platform on an IMU-Based Quadcopter Drone : Telkommil - Supadmana Muda , Nur Rachman; Rio Prabowo, Choirul (Pustaka Poltekad, 2025)
The development of drone technology has driven innovation in the integration of surveillance and weapons systems. This research designs and builds a First Person View (FPV) camera gimbal controller system that can be synchronized directly with the movement of the NR version of the SS2 weapon platform on a quadcopter drone. This system utilizes an Inertial Measurement Unit (IMU) sensor to read the drone's orientation and adjust the gimbal position in real-time to maintain alignment with the target. Tests were conducted at various maneuver angles to verify the gimbal's accuracy, stability, and response to drone movements. The results show accurate synchronization with minimal latency. This controller system uses an STM32 microcontroller and an MPU-6050 IMU sensor as its main components, combined with precision servo motors for gimbal axis drive. The FPV camera is calibrated to remain focused on the SS2 weapon barrel in all orientation conditions. This system integration allows operators to monitor and accurately direct targets remotely via FPV video. Test data shows that the system's stability is maintained even under high vibration conditions and extreme movements. The implementation of this system has great potential for application in tactical military drone applications and security surveillance.